The influence of land area, planting area, and harvested area on rice production in Majalengka regency in 2014-2023 - Shinta, Nazma; Bakhri, Syaeful; Saefulloh, Eef (Institute of Computer Science (IOCS), 2025)
This research aims to determine the effect of land area, planting area and harvest area on production results in Majalengka Regency in 2014-2023. The method used in this research is quantitative using decondary data in the form of a time series from 2014-2023. The data obtained in this research is data obtained from BPS and the Food Security, Agriculture and Fisheries Service. The method used in this research is a multiple linear regression analysis method. The results of this research show that: 1) Land area has a negative and significant effect on rice production results in Majalengka Regency, this means that increasing land area does not always increase rice production, possibly due to other factors sysh as soil fertility, use of technology or suboptimal agricultural management 2) Planting area has a positive and significant effect on rice production results in Majalengka Regency, this means that the wider the planted land, the higher the rice production 3) Harvested area has a positive and significant effect on rice production results in Majalengka Regency, this means that the wider the harvested area, the higher the rice production. These findings can be a reference for the development of agricultural policies in Majalengka Regency, Such as agricultural intensification and efficient input subsidies